2016
DOI: 10.14236/ewic/eva2016.23
|View full text |Cite
|
Sign up to set email alerts
|

Species Explorer: An interface for artistic exploration of multi-dimensional parameter spaces

Abstract: This paper describes Species Explorer, an interface to allow creative exploration of generative systems with multi-dimensional parameter spaces. The system combines both evolutionary and machine learning approaches. It was originally designed to assist creating work for the author's 'Cellular Forms' and 'Hybrid Forms' series, where a large number of parameters are used to yield emergent results, but is a general framework that could be applied to many other systems.Generative art. Evolutionary design. Machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Currently the following creation methods are provided. For more technical detail see (Lomas 2016 These provide a flexible palette of different methods for generation of new parameter values. In the author's experience using the system, he has found that different techniques are appropriate depending on his current intent.…”
Section: Species Explorermentioning
confidence: 99%
“…Currently the following creation methods are provided. For more technical detail see (Lomas 2016 These provide a flexible palette of different methods for generation of new parameter values. In the author's experience using the system, he has found that different techniques are appropriate depending on his current intent.…”
Section: Species Explorermentioning
confidence: 99%
“…Digital Art, Culture and Heritage: New constructs and consciousness Jonathan P. Bowen, Tula Giannini, Rachel Ara, Andy Lomas & Wonderland (1999). Lomas has previously presented at EVA London Conferences (Lomas 2016;Bowen et al 2018b).…”
Section: Title: What Do Digital Artists Do All Day?mentioning
confidence: 99%
“…In 2014, his work Cellular Forms won The Lumen Prize Gold Award. He is a previous presenter and exhibitor at the EVA London conference (Lomas 2016;Papadimitriou et al 2017).…”
Section: Andy Lomasmentioning
confidence: 99%